Ancrage spatial d’un nouveau référent dans le récit en français et en chinois : perspective informationnelle et organisation discursive - Arnaud Arslangul (Discours)
The role of entities used as spatial point of reference in narration has been scarcely discussed in the referential introduction literature. This study focuses on the anchoring of new protagonists in the spatial setting of narrative discourse. It is a contrastive and experimental study, based on an analysis of a corpus elicited from a visual stimulus with speakers of French and Chinese (N = 48). The results reveal different choices of informational perspectives and discourse organisation between the two groups. French speakers introduce the spatial points of reference the same way as the new protagonists by means of a canonical predicative construction and assign the preverbal position to the agent subject of the utterance. They thus place the protagonists at the center of the perspective and the discourse. In contrast, Chinese speakers introduce the spatial points of reference, as well as the new protagonists, in the postverbal position of a presentative construction, and attribute the preverbal position to the topic and locative subject of the utterance. They attribute an important role to the locative phrase in discourse coherence. This difference can be explained by the preeminence of the locative subject in Chinese and the tendency of Chinese to adapt the syntactic structure of the utterance to the pragmatic topic-focus order.